2016
DOI: 10.1111/jace.14616
|View full text |Cite
|
Sign up to set email alerts
|

Flash‐sintering of magnesium aluminate spinel (MgAl2O4) ceramics

Abstract: The sintering behavior of commercially available MgAl2O4 spinel was investigated under DC electric field in a range of 0 and 1000 V/cm. Flash‐sintering results in densification close to theoretical density at 1410°C under the DC field of 1000 V/cm, in comparison to the higher sintering temperature of 1650°C in case of conventional sintering. It was observed that the fields less than 750 V/cm had no significant effect on the densification behavior. An abrupt increase in power dissipation was observed correspond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
32
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 63 publications
(148 reference statements)
3
32
1
Order By: Relevance
“…The steep increase in the specimen current indicated the onset of the flash sintering in the ZrO 2 specimen. The hybrid behavior where the specimen sinters initially by FAST and then transitions to flash has been reported in the flash sintering of dielectric materials such as MgO doped Al 2 O 3 , Y 2 O 3 , and MgAl 2 O 4 . After the isothermal sintering for 3 hours, the linear shrinkages of more than 20% were observed in both of the materials; the relative density of the specimens was about 98% just after the isothermal sintering for 3 hours.…”
Section: Resultsmentioning
confidence: 65%
“…The steep increase in the specimen current indicated the onset of the flash sintering in the ZrO 2 specimen. The hybrid behavior where the specimen sinters initially by FAST and then transitions to flash has been reported in the flash sintering of dielectric materials such as MgO doped Al 2 O 3 , Y 2 O 3 , and MgAl 2 O 4 . After the isothermal sintering for 3 hours, the linear shrinkages of more than 20% were observed in both of the materials; the relative density of the specimens was about 98% just after the isothermal sintering for 3 hours.…”
Section: Resultsmentioning
confidence: 65%
“…[2][3][4][5][6][7][8][9] Unfortunately, flash sintering does not provide excellent uniformity and flashed compacts tend to possess heterogeneous grain sizes between the cathode and anode areas. [10][11][12] For example, Yoshida and coworkers analyzed the grain size distribution of flash-sintered MgAl 2 O 4,13 showing that its heterogeneous grain size was closely related to the diffusion of Mg ions caused by the direct-current (DC) electric field. Other research has shown that grain orientation occurs during sintering under an electric field, 14 with the grain orientation tending to align along the preferred flow path of oxygen ions in undoped ZrO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Flash sintering was first reported in 2010, where 3 mol% stabilized zirconia (3YSZ) was shown to sinter in <5 seconds at a furnace temperature of 850°C at field of 120 V/cm . Since then the method has been shown to apply to various ceramic materials, including, among others, titania (TiO 2 ), yttria (Y 2 O 3 ), Mg‐doped alumina (Al 2 O 3 ), zinc oxide (ZnO), and magnesium aluminate spinel (MgAl 2 O 4 ) …”
Section: Introductionmentioning
confidence: 99%